2019
DOI: 10.1155/2019/9437043
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Hepatitis—Immunologically Triggered Liver Pathogenesis—Diagnostic and Therapeutic Strategies

Abstract: Autoimmune hepatitis (AIH) is a severe liver disease that arises in genetically predisposed male and female individuals worldwide. Diagnosis of AIH is made clinically applying diagnostic scores; however, the heterotopic disease phenotype often makes a rapid determination of disease challenging. AIH responds favorably to steroids and pharmacologic immunosuppression, and liver transplantation is only necessary in cases with acute liver failure or end-stage liver cirrhosis. Recurrence or development of de novo AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 197 publications
(212 reference statements)
2
83
0
11
Order By: Relevance
“…AIH is mainly characterized by liver inflammation, which is essentially a chronic and unresolved liver inflammatory damage (6). Inflammation is an energy-expensive biological process that requires a large amount of energy and intermediary metabolites for the synthesis of inflammatory factors and immune response (7).…”
Section: Introductionmentioning
confidence: 99%
“…AIH is mainly characterized by liver inflammation, which is essentially a chronic and unresolved liver inflammatory damage (6). Inflammation is an energy-expensive biological process that requires a large amount of energy and intermediary metabolites for the synthesis of inflammatory factors and immune response (7).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we speculated that the elevated serum IgG4 levels observed during the pathogenesis of AIH may occur because of IgG4 binding to the PD-1 receptor on the surface of TH17 cells, which could block the PD-1 pathway-mediated inhibition of TH17 cell proliferation and cytokine generation, thereby promoting TH17 cell proliferation and increased production of related cytokines and causing the higher prevalence of cirrhosis observed in AIH patients with elevated serum IgG4 levels. Previous studies reported [ 6 , 7 ] that the increase in the number of TH17 cells in AIH was associated with the degree of liver fibrosis, and in vitro studies also confirmed that deficiencies in IL-17A and IL-17A receptors could reduce the liver fibrosis caused by CCl4 and bile duct ligation in mice [ 33 ]. Other studies [ 34 ] also showed that serum IL-17A and IL-22 levels were positively correlated with liver injury in AIH.…”
Section: Discussionmentioning
confidence: 68%
“…An existing study [ 6 ] suggests that interleukin (IL) 17 can stimulate a variety of types of nonparenchymal liver cells to secrete proinflammatory cytokines and chemokines to induce and promote liver inflammation in liver disease. IL-17 also promotes liver fibrosis by activating hepatic stellate cells [ 7 ]; therefore, we explored the differences in TH17-related cytokines between the elevated serum IgG4 group and the normal group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune cells that accumulated in the portal/periportal lesions were composed of CD4 + T cells, CD8 + T cells, CD20 + B cells, CD138 + plasma cells and FOXP3 + Tregs. Thus, various adaptive immune cells infiltrate the portal and periportal lesions of patients with AIH, suggesting that maturation of immune networks in the portal tract is necessary for the development of AIH 33 . In addition, CD4 + T cells and CD20 + B cells accumulated into the lobular lesions of patients with AIH, but not hepatic irAEs or GVHD.…”
Section: Discussionmentioning
confidence: 99%